POSSIBILITIES OF USING IMPROVED MODERN TECHNOLOGIES IN THE DEVELOPMENT OF CHILDREN’S ORAL COMMUNICATION SKILLS THROUGH THE MEDIUM OF FOLK ART - Farangis Murodova Ganisherovna (Galaxy International Interdisciplinary Research Journal, 2024)
This article reveals the effectiveness and significant aspects of developing artistic speech and oral communication skills of students of preschool educational organizations by means of mnemonic technology using folklore examples.